Electrooxidation of Phenylhydrazine on Nanostructured Co-Mo Alloy Electrodes in Alkaline Medium - Mehdi Abdolmaleki (Nanochemistry Research)
In this work, we investigated the electrocatalytic activity of electrodeposited cobalt and CoMo alloy electrodes towards the oxidation of phenylhydrazine in 1 M sodium hydroxide aqueous solution. A previously proposed nontoxic tartrate electrolyte was employed to electrodeposit alloys. Electrochemical methods such as cyclic voltammetry (CV), chronoamperometry (CA), and electrochemical impedance spectroscopy (EIS) were used to study the electrooxidation of phenylhydrazine. When compared to pure cobalt electrodes, the voltammetric data for cobalt-molybdenum alloy electrodes indicated a lower peak potential and a higher peak current density. According to the EIS results, the polarization resistance of the Co-Mo alloy electrodes was much lower compared to the pure Co in 0.1 M phenylhydrazine basic solution. The CA results demonstrated that Co-Mo electrodes had greater stability than cobalt electrode. The Co-25 at % Mo and Co-33 at % Mo electrodes had higher catalytic activity among other synthesized electrodes for phenylhydrazine oxidation in an alkaline medium, the former being the best electrocatalysts for the phenylhydrazine electrooxidation.